Natural monopoly and distorted competition: Evidence from unbundling fiber-optic networks - Naoaki Minamihashi (Bank of Canada, 2012)
Can regulation solve problems arising from a natural monopoly? This paper analyzes whether unbundling, referring to regulations that enforce sharing of natural monopolistic infrastructure, prevents entrants from building new infrastructure. It models and estimates a dynamic entry game to evaluate the effects of regulation, using a dataset for construction of fiber-optic networks in Japan. The counterfactual exercise shows that forced unbundling regulation leads to a 24% decrease in the incidence of new infrastructure builders. This suggests, therefore, that when a new technology is being diffused, regulation to remove a natural monopoly conversely involves risks that regulated monopolists' shares will increase.
Keywords: K23; L43; L96; 330; Market structure and pricing; Productivity